Extensión Universitaria y Vinculación Comunitaria de la Universidad Técnica de Cotopaxi en el año 2014. Propuesta alternativa de reestructuración en base a proyectos de gestión por Unidades Académicas. - Banda Casa, Mario Agustín (2015)
Linking Social Community of Cotopaxi Technical University, In the evaluation by the Council of Evaluation, Accreditation and Quality Assurance of Higher Education in 2013, It has not reached the necessary score in the corresponding indicator to contribute to the Institutional overall rating. In function of this reality, the present work focuses on basic theorical aspects as Education Model, Academic Management, and Curriculum, identifying te management of the institution. Moreover it is supplemented with elements as Comunity Social Linking, the Plan, Program and Linking Project. It has been proposed as targets, generating the necesary tolos, establish a development methodology, and select ction guidelines for acedemic units to design, execution and evaluation to Projects of Community Social Linking. For all this has been used bibliographic methods in search of information, The app of the inductive and deductive method to support collection of information through technical poll. Analysis and Synthesis was used to proposed guidelines for action of Linking. As a result it possible to meet the need of student and teacher with respect to knowledge about of social research. Also it was stablished that the student has low relevance level respect this proccess. It was possible to identify the need of framework of guidelines in the proccess of Project design adjusted to objetives of National Plan of Good Living. The results of this research benefit the participating students and teachers coordinators who can effectively implement the linking process.